KEANEKARAGAMAN JENIS KANTONG SEMAR (Nepenthes spp) DALAM KAWASAN HUTAN TANAMAN INDUSTRI PT. BHATARA ALAM LESTARI KABUPATEN MEMPAWAH PROVINSI KALIMANTAN BARAT - Septiani, Oktaviana Septiani; Herawatiningsih, Ratna; Manurung, Togar Fernando (Universitas Tanjungpura, 2018)
Nepenthes is a unique and rare plants that exist in Indonesia, as the plants listed are those species that threatened extinct. Reseach aims to determine the Nepenthes species diversity in Industrial Plantation Forest Areas Sustainable Natural PT. Bhatara Alam Lestari Mempawah district of West Kalimantan, The method used was survey metho. Field data collection using a single swath in purposive sampling, then the data were analyzed by using the formula diversity index Shannon-Wiener equation. The result shows in Industrial Plantation Forest Sustainable Natural PT.Bhatara found 7 speci these species are Nepenthes of Nepenthes ampullaria, Nepenthes rafflesiana, Nepenthes pilosa, Nepenthes reinwardtiana, Nepenthes xneglecta, Nepenthes bicalcarata and Diversity hirsute. Indeks Nepenthes highest in rafflesiana Nepenthes species by value (H = 0.1376), with a value Nepenthes ampullaria (H = 0.1200), Nepenthes xneglecta value (H=0.074), and the lowest for the Diversity Index Nepenthes pilosa species by value (H = 0.0076).Keywords: Diversity type, Nepenthes, Nepenthes ampullaria, rafflesiana. Purposive Sampling.